The Role of Social Capital in Economic Development of Transition Countries - Parts, Eve (Ekonomika, 2004)
Current interest in the concept of social capital in the field of economic development stems from the limitations of prevailing economic approach toward the achievement of the basic developmental goals - sustained growth, equity, and democracy. The purpose of the current study is to analyse the effects of social capital and related institutional factors on the development process. Both theoretical and empirical findings suggest that these effects could be different in transition countries, compared to mature market economies.